Fabrication of wrist-like SMA-based actuator by double smart soft composite casting. (15th October 2015) - Rodrigue, Hugo; Wei, Wang; Bhandari, Binayak; Ahn, Sung-Hoon
Abstract: A new manufacturing method for smart soft composite (SSC) actuators that consists of double casting a SSC actuator to produce an actuator with non-linear shape memory alloy (SMA) wire positioning is proposed. This method is used to manufacture a tube-shaped SSC actuator in which the SMA wires follow the curvature of the tube and is capable of pure-twisting deformations while sustaining a cantilever load. The concept is tested by measuring the maximum twisting angle and a simple control method is proposed to control the twisting angle of the actuator. Then, a soft robotic wrist with a length of 18 cm is built, its load-carrying capability is tested by measuring the cantilever force required for deforming the actuator, and its load-carrying capability during actuation is tested by loading one end with different objects and actuating the actuator. This wrist actuator shows good repeatability, is capable of twisting deformations up to 25° while holding objects weighing 100 g, and can sustain loads above 2 N without undergoing buckling.